Non-thermal regimes of laser annealing of semiconductor nanostructures: crystallization without melting - Mirza, Inam; Bulgakov, Alexander V.; Sopha, Hanna; Starinskiy, Sergey V.; Turčičová, Hana; Novák, Ondřej; Mužík, Jiří; Smrž, Martin; Volodin, Vladimir A.; Mocek, Tomáš; Macak, Jan M.; Bulgakova, Nadezhda M. (Frontiers in Nanotechnology, 2023)
As-prepareddeposited/synthesized nanostructured semiconductor materials are usually found in an amorphous form, which needs to be converted into a crystalline one for improving electronic properties and achieving enhanced application functionalities. The most utilized method is thermal annealing in a furnace, which however is time-and energy-consuming and not applicable for low-temperature melting substrates. An alternative is laser annealing, which can be carried out in a relatively short time and, additionally, offers the possibility of annealing localized areas. However, laser-annealed nanostructures are often distorted by melting, while preserving the as-prepared morphology is essential for practical applications. In this work, we analyze conditions of nonthermal ultrafast laser annealing of two kinds of nanostructures: anodic TiO2 nanotube layers and Ge/Si multilayer stacks. For both cases, regimes of crystallization have been found, which yield in preserving the initial nanomaterial morphologies without any melting signs. On these examples, ultrafast non-thermal mechanisms of structural material transformation are discussed, which can provide new opportunities for conversion of amorphous semiconductor nanomaterials into a desired crystalline form that is of high demand for existing and emerging technologies.